INTERCULTURAL COMMUNICATION BARRIERS OF NEW STUDENTS IN VIRTUAL MEDIA - Medan Muslimin; Muhammad Ahsan Rusydi; Florencia Dwi Aristya (Jurnal Scientia, 2023)
Self-adjustment is a common problem encountered by new students. Almost all of them are related to adjusting to the unique situation in higher education. The existence of differences in cultural backgrounds causes differences in perceptions among students, especially in interactions through virtual media. This research aims to identify barriers to communication between cultures among new students at the LSPR Communication & Business Institute when interacting through virtual media. This study used qualitative research methods. Data collection is done by collecting information from primary data and secondary data. Preliminary data were obtained from interviews and direct field observations, while secondary data were obtained from references or previous research journals. The study results show that technological, psychological, environmental, language and other factors cause new students' intercultural communication barriers in virtual media. This research implies that various parties, especially the campus, can use it as a reference to overcome intercultural communication barriers between ethnic groups when interacting through virtual media.